Inter-Robot Data Exchanged for Locomotion and Localisation - Makhtar, Muhammad Makram (Universiti Teknologi PETRONAS, 2016)
Multi robot is a group of robot (two or more) that works together to do certain task. The task given to the robots maybe impossible to be done by only one robot but with several similar robots working together, the task can be easily done. In order to work together, they have to communicate with each other and the best way to communicate is through wireless communication. Multi robots need to know certain information about other robots such as the location, locomotion and orientation. This is essential to avoid collision and doing the same things during the mission. In this project, two mobile-based robot is built to follow instruction given through a master computer and they need to report their location to the master computer and also send the location to one another. The robot is built using a simple platform with DC motor attached. The Arduino Mega is used as the microcontroller and XBee wireless module is used for the robots to communicate wirelessly.